Empleo de las tic’s en el desarrollo académico como parte del proceso pedagógico para la enseñanza de kichwa, como lengua autóctona, en los estudiantes de educación básica de la Universidad Técnica de Cotopaxi, extensión La Maná, año 2014 - Rivera Carrera, Guadalupe del Rocío (2015)
The main purpose of the present research is applying of TIC’s in the teaching-learning process for teaching Kichwa. At present few teachers use as a practical tool in the daily work for reduces, synthesizing the teaching is for this reason that propose the use of an interactive CD as a tool to help strengthen into education in as students of the School of Basic Education because they are the future teacher of our province since with technological advances have new teaching tools with which the teacher must be competent and coupled to bilingual education needs and organizing investigative skills, critical thinking, creative, communicative, collaborative, participatory and lifelong learning.